IMPLIKASI HUKUM DAN SOSIAL DARI KASUS KORUPSI DI PT TIMAH (TBK) - Pramitha, Davina Kezhya; Zulfiani, Anita (LPPM Universitas Bina Bangsa, 2024)
The corruption case involving PT Timah attracted widespread attention due to its significant impact on legal and social aspects. This research aims to investigate the implications of criminal acts of corruption for various related parties and society in general. Through normative juridical methods with library research, data was obtained from library materials and a statutory approach to understand how the corruption case at PT Timah affected various legal and social aspects. The corruption case at PT Timah had a significant impact on a number of parties, including company employees, investors, suppliers and business partners. Economically, this case caused financial losses for the company and reduced investor confidence in the mining sector. Meanwhile, socially, this corruption case causes a lack of public trust in the integrity of companies and the legal system as a whole. Apart from that, this research also identifies the chronology and legal implications caused by several factors such as lack of internal supervision, unhealthy organizational culture, and low awareness of business ethics and legal compliance. Based on this, it reminds us how necessary it is to improve the internal monitoring system, transparency and culture of integrity in order to prevent and handle corruption cases at PT Timah and related sectors